IDENTIFICATION OF NATURAL RESOURCES IN THE DISTRICT MERAUKE - Ferdinand C Situmorang (Musamus Journal of Agribusiness, 2019)
The availability of natural resources owned Merauke district has the potential but has not been used optimally. Merauke District is a district that has a variety of potential natural resources such as: agriculture, fisheries, animal husbandry, tourism and forestry. Management of natural resources in Merauke is still not able to provide welfare for the people of Merauke and have not been able to contribute original income. With the identification of the natural resources that exist in Merauke so that it can provide information about the natural resources that exist to the general public, especially for investors who wish to cooperate with the Regional Government of Merauke for the progress of development in order to create welfare for people in Merauke. Keywords: Potential, Natural Resources, Merauke